Performance of MR-Deduster: a case study of a palm oil mill plant - Mohd. Yusof, Mohd. Rashid (Trans Tech Publications, 2013)
Multi-cyclones is commonly usedin the palm oil mill industry as particulate pollution arrestor. However, its ability in capturing particulate matter (PM) especially the fine particulate size fraction is limited. Thus, study has been carried out to investigate and predict the performance of MR-deDuster, a multi-cyclones unit developed as particulate emission control device in palm oil mill plant. The MR-deDuster is intentionally developed to overcome particulate emission issue facing by industries that generate particulate especially the palm oil mill industry. A number of semi-empirical theories were used to predict the performance of MR-deDuster. Based on the prediction, the MR-deDuster manages to capture particulate size 3.8µm at 50% particulate collection efficiency. The MR-deDuster also manages to achieve more than 90% for total particulate collection efficiency with low pressure drop.